In silico evidence implicating novel mechanisms of Prunella vulgaris L. as a potential botanical drug against COVID-19-associated acute kidney injury - Yang, Xue-Ling; Wang, Chun-Xuan; Wang, Jia-Xing; Wu, Shi-Min; Yong, Qing; Li, Ke; Yang, Ju-Rong (Frontiers in Pharmacology, 2023)
COVID-19-associated acute kidney injury (COVID-19 AKI) is an independent risk factor for in-hospital mortality and has the potential to progress to chronic kidney disease. Prunella vulgaris is a traditional Chinese herb that been used for the treatment of a variety of kidney diseases for centuries, could have the potential to treat this complication. In this study, we studied the potential protective role of Prunella vulgaris in COVID-19 AKI and explored its specific mechanisms applied by network pharmacology and bioinformatics methods. The combination of the protein-protein interaction (PPI) network and Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) en-richment -target gene network revealed eight key target genes (VEGFA, ICAM1, IL6, CXCL8, IL1B, CCL2, IL10 and RELA). Molecular docking showed that all these eight gene-encoded proteins can be effectively bound to three major active compounds (quercetin, luteolin and kaempferol), thus becoming potential therapeutic targets. Molecular dynamics (MD) simulation also proofs the binding stability of RELA-encoded protein (NF-κB) with quercetin and luteolin. Together, our data indicate that IL6, VEGFA, and RELA were the potential drug targets, and inhibition of the NF-κB signaling pathway was found to be the most critical therapeutic measure.